1997
DOI: 10.1177/096120339700600905
|View full text |Cite
|
Sign up to set email alerts
|

Lack of NK cells in lupus patients with renal involvement

Abstract: We have previously shown that patients with SLE have significantly lower percentages and absolute numbers of NK(CD3-/CD16+56) cells in their peripheral blood compared with normals. Patients with active disease had very low levels of NK cells and the reduction was also associated with patients who had renal involvement. We have now performed a serial study immunophenotyping 11 patients with SLE and renal involvement using dual colour immunofluorescence and flow cytometry. Patients were tested every three months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 19 publications
(1 reference statement)
7
40
1
Order By: Relevance
“…9,28 Several authors have underlined how a`normal' non-MHC-restricted cytotoxic activity, both of NK cells and of T lymphocytes, is important in preventing autoimmune processes. 1,18,29 An alteration of this component of the immune response seems to be important in the development of SLE since NK cells are decreased signi®cantly in active disease states and in patients with renal involvement. 17,18 A signi®cantly lower frequency of gad T cells, that are known to belong mainly to the cytotoxic subset, 6 has also been found in PBMCs of SLE patients as compared to normal subjects, although no correlation has been reported with either clinical or laboratory indices of disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,28 Several authors have underlined how a`normal' non-MHC-restricted cytotoxic activity, both of NK cells and of T lymphocytes, is important in preventing autoimmune processes. 1,18,29 An alteration of this component of the immune response seems to be important in the development of SLE since NK cells are decreased signi®cantly in active disease states and in patients with renal involvement. 17,18 A signi®cantly lower frequency of gad T cells, that are known to belong mainly to the cytotoxic subset, 6 has also been found in PBMCs of SLE patients as compared to normal subjects, although no correlation has been reported with either clinical or laboratory indices of disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…19 A decreased number of NK cells seems, in fact, to play an important role in the course and prognosis of SLE and to re¯ect increased disease activity and renal involvement. 17,18 Few con¯icting data exist concerning the possible involvement of TCR gad positive lymphocytes, able to mediate a cytotoxic function similar to that of the NK cells. 13 No signi®cant correlation has indeed been found, so far, in SLE, among this T cell subset and other clinical or laboratory measurements of disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…58 However, in systemic lupus erythematosus (SLE), patients show a variable and moderate reduction of NK-cell numbers along with reduced CD4 + CD25 + Treg cells. 59,60 The function of NK cells is downregulated in these patients and there is a shift from the CD56 dim population to the CD56 bright subset. 61,62 It is also indicated that NK cells in these patients have a reduced cytotoxic effect.…”
Section: Role In Various Disease Conditionsmentioning
confidence: 99%
“…Located within the 4p15 region is the gene encoding lymphocyte differentiation antigen CD38 (ADP ribosyl cyclase/cyclic ADPribose hydrolase), formerly known as OKT10. Several studies have shown increased levels of CD38 expressing T and B cells in SLE patients compared to the controls [108][109][110][111]. Studies of mice deficient in CD38 show alterations of the humoral immune responses [112].…”
Section: Linkage Studies Of Human Slementioning
confidence: 99%